Architectures de terre et de bois L'habitat privé des provinces occidentales du monde romain. Antécédents et prolongements : Prohistoire, Moyen Age et quelques expériences contemporaines - Lasfargues, Jacques (Documents d'archéologie française, 1985)
Earth and wood constructions of the Roman era were, until several years ago, very little known. Recent excavations have provided us with considerable information. This work attempts to answer primary questions such as : are these protohistorical survivals ? what construction techniques were used ? what socio-economic conditions do they correspond to ? The textual and archaeological approach go along with informationobtained by contemporary experiments.